2013
DOI: 10.1002/anie.201309207
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Cp‐Rhodium(III)‐Catalyzed Asymmetric Hydroarylations of 1,1‐Disubstituted Alkenes

Abstract: Metal-catalyzed functionalizations at the ortho position of a directing group have become an efficient bond-forming strategy. A wide range of transformations that employ Cp*Rh(III) catalysts have been described, but despite their synthetic potential, enantioselective variants that use chiral versions of the Cp* ligand remain scarce (Cp*=pentamethyl cyclopentadienyl). Cyclopentadienyl compounds with an atropchiral biaryl backbone are shown to be suitable ligands for the efficient intramolecular enantioselective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
83
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(88 citation statements)
references
References 73 publications
(18 reference statements)
1
83
0
4
Order By: Relevance
“…More recently, Cramer and coworkers reported an asymmetric version of this chemistry to access functionalized chiral dihydrobenzofurans that possess a quaternary stereocenter using chiral rhodium catalyst (Scheme 6.13) [23]. They found that O-tethered substrate 54 was deuterated more quickly than metamethyl-substituted derivative 55.…”
Section: Mementioning
confidence: 99%
“…More recently, Cramer and coworkers reported an asymmetric version of this chemistry to access functionalized chiral dihydrobenzofurans that possess a quaternary stereocenter using chiral rhodium catalyst (Scheme 6.13) [23]. They found that O-tethered substrate 54 was deuterated more quickly than metamethyl-substituted derivative 55.…”
Section: Mementioning
confidence: 99%
“…Using another Cp derivative as a chiral ligand on Rh, high enantioselectivities were achieved at room temperature, demonstrating that the intramolecular alkene insertion is a more efficient process than the corresponding intermolecular variant. 137 Ma's group devised a transformation combining allene carborhodation and subsequent cyclization with a tethered olefin to prepare polycyclic products featuring eight-membered lactams. 138 …”
mentioning
confidence: 99%
“…[4] Enantioselective C À Hf unctionalization has recently attracted much attention for the synthesis of complex molecules including chiral stereocenters. [5] In this context, the group of Cramer reported that Rh III [6] and Ir III[7] complexes bearing precisely designed chiral Cp x ligands enabled catalytic asymmetric CÀHf unctionalization reactions. [8] The groups of You [9] and Antonchick and Waldmann [10] also developed different types of chiral Cp x ligands.T hese designed Cp x ligands greatly facilitated the development of enantioselective CÀHf unctionalization reactions (Scheme 1a).…”
mentioning
confidence: 99%